Empathy, Shared Intentionality, and Motivation by Moral Reasons - Hourdequin, Marion (2012)
Internalists about reasons generally insist that if a putative reason, R, is to count as a genuine normative reason for a particular agent to do something, then R must make a rational connection to some desire or interest of the agent in question. If internalism is true, but moral reasons purport to apply to agents independently of the particular desires, interests, and commitments they have, then we may be forced to conclude that moral reasons are incoherent. Richard Joyce (2001) develops an argument along these lines. Against this view, I argue that we can make sense of moral reasons as reasons that apply to, and are capable of motivating, agents independently of their prior interests and desires. More specifically, I argue that moral agents, in virtue of their capacities for empathy and shared intentionality, are sensitive to reasons that do not directly link up with their pre-existing ends. In particular, they are sensitive to, and hence can be motivated by, reasons grounded in the desires, projects, commitments, concerns, and interests of others. Moral reasons are a subset of this class of reasons to which moral agents are sensitive. Thus, moral agents can be motivated by moral reasons, even where such reasons fail to link up to their own pre-existing ends.
Keywords: Externalism; Internalism; Moral Motivation; Moral Reasons; Shared intentionality; Empathy